A family of high voltage gain quasi‐Δ‐source impedance networks - Hamed Rezazadeh; Mohammad Monfared; Ali Nikbahar; Saeed Sharifi (IET Power Electronics, 2021)
Abstract This paper proposes a class of impedance networks, called quasi‐Δ‐source, as an improvement to the successful Δ‐source one. Compared to their origin, the three proposed networks offer higher voltage gains with a better magnetic circuit utilization and a smooth continuous input current. A lower magnetizing and total inductance required for the Δ‐shaped coupled inductors of the proposed networks allows smaller and cheaper magnetic cores utilization. Also, a lower total power loss of the magnetically coupled elements is another interesting advantage of the proposed networks. Moreover, the total required capacitance of the proposed networks is the same and even slightly lower than that of the conventional Δ‐source one. All these improve the performance of the proposed class of networks with the smaller size of components compared to their conventional competitor. The principles of operation are developed and the theoretical analysis is performed. Also, by using the circuit averaging technique, the small‐signal models of the Δ‐source and the proposed networks are derived as well as their control‐to‐output transfer function is achieved. Finally, the experiments on a 300 W rated power prototype of the proposed networks successfully confirm the theoretical achievements.